KAPASITAS ADSORPSI BEBERAPA JENIS KULIT PISANG TERAKTIVASI NaOH SEBAGAI ADSORBEN LOGAM TIMBAL (Pb) - Putu Eka Purnama; I Gusti Ayu Kunti Sri Panca Dewi; Ketut Ratnayani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
Adsorption capacity of various types of banana skin (green, kepok and susu) activated with NaOH as adsorbents for lead (Pb) has been studied. This research consisted of several steps included determination of the surface area of activated and unactivated adsorbents, equilibrium time, adsorption isotherms and adsorption capacity of adsorbents from green, kepok and susu banana skins activated with NaOH . The results showed that adsorbents from green, kepok and susu banana skin activated with NaOH had surface were of 36.2181 m2/g, 35.5531 m2/g and 35.8378 m2/g respectively. On the other hand, the surface area of unactivated adsorbents of green, kepok and susu banana skin were 35.3105 m2/g, 35.3199 m2/g, and 35.7928 m2/g respectively. Equilibrium time for green, kepok and susu banana skin adsorbents activated with NaOH were 30; 30 and 90 minutes. Adsorption isotherms of adsorbents from green, kepok and susu banana skin activated with NaOH were at concentration 100 ppm. Adsorption capacity of activated adsorbents from green banana, kepok banana and susu banana skin were 7.022 mg/g, 5.3078 mg/g and 6.6850 mg/g respectively.